2008
DOI: 10.3171/jns/2008/108/2/0281
|View full text |Cite
|
Sign up to set email alerts
|

State and trait anxiety and depression in patients with primary brain tumors before and after surgery: 1-year longitudinal study

Abstract: Patients affected by brain tumors frequently experience affective disorders. After brain surgery, a depressive state can develop. The psychometric assessment could be useful in these patients for quick recognition of psychological disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 27 publications
5
71
1
5
Order By: Relevance
“…This is in concordance with Goebel et al, who were able to show that patients with meningiomas developed psychological comorbidities similar to patients with high-grade gliomas [17], but in contrast to their findings, supported by results of others [11,23], we found scores to improve in both groups over time with earlier peak BDI scores in patients with extraaxial tumors (3 vs. 6 months) and significant changes over time in patients with intraaxial tumors (p = 0.001).…”
Section: Depression After Surgerysupporting
confidence: 89%
See 2 more Smart Citations
“…This is in concordance with Goebel et al, who were able to show that patients with meningiomas developed psychological comorbidities similar to patients with high-grade gliomas [17], but in contrast to their findings, supported by results of others [11,23], we found scores to improve in both groups over time with earlier peak BDI scores in patients with extraaxial tumors (3 vs. 6 months) and significant changes over time in patients with intraaxial tumors (p = 0.001).…”
Section: Depression After Surgerysupporting
confidence: 89%
“…has been published to date investigating anxiety and depression in patients with meningiomas after surgical resection [17]. Litofsky et al and D'Angelo et al investigated the course of depressive symptoms and anxiety after glioma surgery [11,23]. Knowing that suicidal ideation (SI) increases in patients with cancer compared to the general population [34,49], especially in cancers associated with physical impairment and dismal prognosis [2,3], one might assume that the incidence of SI in patients with malignant brain tumors is high.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Owing to the high integration of the brain structures, it is difficult, and perhaps incorrect, to tailor a psychiatric disorder, or even a psychiatric symptom, to a discrete brain area: it appears that, opposite to some neurological findings, the appearance of a psychological suffering is to be addressed to a set of incorrect integrative operations between different brain areas, rather than to a focused lesion. Anyway, it must be reported that this is not always true: there are cases of a depressive disorder caused by a focused neurological damage, such as a tumor, or a surgical wound, but even in those cases, the same symptomatology, as far as it can be depicted from the clinical observation, can be associated with wounds that lay in diverse parts of the brain [D'Angelo et al, 2008]. Moreover, non-responsive OCD disorders can be treated by cingulotomy or focused deep brain stimulation, but these treatments usually cannot predict the 100% of reduction of symptoms [Rauch et al, 2001[Rauch et al, , 2006Sachdev et al, 2001;Guarnieri et al, 2005], suggesting that the mechanism that leads to OCD only partially lays within a single brain area.…”
mentioning
confidence: 99%
“…It is true that some groups have found women with brain tumours to be more likely than men to become depressed [2,3]. However other researchers have not, including one of the authors of the review [4][5][6].…”
mentioning
confidence: 99%